Strategi Pemasaran Pada Usaha Kecil Menengah - Yanti; Hartono; Ulfa Jamilatul Farida (Jurnal Ekonomi dan Bisnis Digital, 2025)
Small and Medium Enterprises (SMEs) play a crucial role in supporting local economic development, particularly in growing regions such as Sangatta City. This study aims to examine the implementation of marketing strategies by SMEs operating in the Taman Venus area of Sangatta and to analyze their impact on business growth and income enhancement. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that SMEs apply five main marketing strategies: product, pricing, distribution, promotion, and customer satisfaction. These strategies are generally implemented in a practical and intuitive manner without formal planning, yet they have proven effective in attracting customers and increasing income. The strategic location of the business and strong social interactions also contribute to the success of these marketing efforts. However, weaknesses remain in the use of digital promotion and data-based business management. Therefore, efforts to strengthen managerial capacity and adopt digital marketing tools are needed to support the long-term competitiveness and sustainability of SMEs in the area...